Psychological Terror and Exploitation in Craig Mazin’s Chernobyl (2019) TV Series: A Marxist Literary Criticism - Condro Wati, Salsabila (Universitas Negeri Surabaya, 2025)
This study analyses the representation of psychological terror and labor exploitation in Chernobyl (2019). This study adopted a Marxist theoretical approach, following Althusser’s perspective with the concept of the State Ideological Apparatus (SIA) and the State Repressive Apparatus (SRA). The research conduct content analysis on five episode: ‘1:23:45’, ‘Please Remain Calm’, ‘Open Wide, O Earth’, ‘The Happiness of All Mankind’, and ‘Vichnaya Pripyat’. The study findings indicate that the Soviet government in the Chernobyl TV series used psychological terror through strict surveillance, information manipulation, and ideological pressure to impose compliance. Scenes such as Sitnikov’s death and the dangerous tasks performed by the divers depict how the state packaged exploitation within a narrative of heroism. The study also shows that interventions against scientists like Legasov and Khomyuk were a means of state control over truth. The Chernobyl TV series works as a critique of authoritarian systems that sustain authority through lies, fear, and violence, thereby pointing to concludes that psychological terror is still a simple way to keep an eye on the workers and keep ideological hegemony in the modern era.